2008
DOI: 10.1359/jbmr.080608
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Measurement May Not Reflect What You Give to Your Patients

Abstract: The recognized index of vitamin D (VTD) status is the measurement of circulating concentrations of 25-OH VTD (25VTD). A concentration of 30 ng/ml 25VTD (75 nM) is considered by many experts as the minimum optimal concentration.(1) There is currently a growing interest in VTD far beyond bone and calcium metabolism, (2) including cancer, immunology, and hypertension, which has caused a recent upsurge in requests for 25VTD evaluation, (3) necessitating the need for accurate measurement.We report here the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 9 publications
(11 reference statements)
0
16
0
3
Order By: Relevance
“…Indeed, although skin exposure to UVB produces vitamin D3 and food sources of vitamin D contain mainly vitamin D3, supplementation is often made with vitamin D2, especially in the USA. As long as vitamin D2 is available, it is mandatory to measure 25VTD with a method that recognizes both 25VTD2 and 25VTD3 in order to avoid underestimation of the vitamin D status and thus potentially lead to overtreatment, and to expensive and stressful explorations (21).…”
Section: Vitamin D Deficiency and ''Desirable'' Serum Valuesmentioning
confidence: 99%
“…Indeed, although skin exposure to UVB produces vitamin D3 and food sources of vitamin D contain mainly vitamin D3, supplementation is often made with vitamin D2, especially in the USA. As long as vitamin D2 is available, it is mandatory to measure 25VTD with a method that recognizes both 25VTD2 and 25VTD3 in order to avoid underestimation of the vitamin D status and thus potentially lead to overtreatment, and to expensive and stressful explorations (21).…”
Section: Vitamin D Deficiency and ''Desirable'' Serum Valuesmentioning
confidence: 99%
“…(6) We have found that administration relative to meal intake can be an additional factor that results in unpredictable serum 25(OH)D levels even when a proper assay is used. We commonly find that patients take the medication on an empty stomach or with a light meal.…”
mentioning
confidence: 99%
“…Nonetheless, unless the laboratorians recognize limitations of their assay, significant confusion can arise. This was nicely illustrated in the case report from Belgium where physicians treated vitamin D deficient patient with vitamin D 2 , while her serum vitamin D levels were measured using the vitamin D 3 assay (34). It is also important to recognize that none of the studies published on comparison of automated immunoassays with LC-MS/MS methodology recruited more than a few patients supplemented with vitamin D 2 .…”
Section: Choice Of Methodsmentioning
confidence: 99%